Influence of strain-hardening on the load-carrying behaviour of bearing type bolted connections. (April 2022) - Studer, Patrick; Taras, Andreas
Abstract: The investigations presented in this paper focus on the hole bearing resistance of symmetric single-bolt connections, taking into account the distinct hardening behaviour of various steel grades and quantifying its impact on the resulting load-carrying behaviour. The main focus of the study was put on the limitation of the hole bearing deformations by defining a corresponding "resistance", which is thus a quantity with the background of an implicit deformation limitation. This represents a further expansion of new regulations, which have currently found their way into the draft version of the part of the Eurocode 3 standard dedicated to the resistance of connections prEN1993-1-8 . In contrast to this draft standard, the specific differences between steels with very pronounced and less pronounced hardening behaviour are dealt with. Experimental investigations were carried out on four different steel grades, each with eight different geometries, in order to investigate the influence of this hardening behaviour on the hole bearing deformations. The paper presents a new approach to define the point on the load-deformation curve between acceptable and excessive deformations. This is defined as a point with a certain slope of the normalised and standardised load-deformation curve, namely the point where the tangent stiffness corresponds to the secant stiffness defined by connecting the origin of the load-deformation point to the point with the peak load. Based on the results of the hole bearing tests in combination with the new approach to define the transition point between acceptable and excessive deformations, an adapted resistance model is presented. In this model, the hardening behaviour of the steel is taken into account, whereby here specifically the ratio fu /fy of tensile strength to yield strength influences the load-bearing behaviour. In addition to laboratory tests, numerical simulations were carried out with an extended range of geometries. This made it possible to create a representative data set with which the proposed model could be verified. It was shown that with the developed proposal a significant improvement of the prediction accuracy can be achieved compared to the resistance model in prEN1993-1-8. The proposed adaptation of the hole bearing verification which takes the fu /fy ratio into account facilitates the optimal use of material and can thus save resources. The format of the hole bearing verification remains almost unchanged, which should simplify its applicability in practice. Graphical abstract: Unlabelled Image Highlights: Experimental and numerical simulations of hole bearing tests on four different steel grades are conducted Influence of the hardening characteristic of the steel on the hole bearing resistance is evaluated Procedure to differentiate between acceptable and excessive deformations is presented An adjusted hole bearing resistance to limit the bearing deformations is determined